Pemahaman Masyarakat tentang Harta BersamaPerspektif Hukum Positif Indonesia - Melinda, Nely; Sakirman (Syakhsiyah Jurnal Hukum Keluarga Islam, 2023)
Joint assets in marriage are a combination of all assets obtained after the formation of marital status through a legal bond and are also defined as assets that are owned by both parties (husband and wife) or assets in joint names that are acquired simultaneously by husband and wife during the marriage takes place. Indonesian Positive Law which consists of Law no. 16 of 2019 concerning Marriage, the Compilation of Islamic Law, and the Civil Code (KUHP) also regulates the use of joint property objects in marriage in harmony with each other, which states that each party has the same rights to joint property and One of the parties can act, such as transferring, donating or selling joint property with the consent of both parties. This research uses field research with qualitative methods which aims to gather information from the people of Central Metro Yosomulyo regarding understanding of joint property using the Indonesian positive law approach as an analytical tool. This research is normative-sociological in nature because this research uses Indonesian Positive Law as a reference, namely making humans or society as objects, by examining the understanding of the Yosomulyo community regarding collective property which is then analyzed by referring to the perspective of Indonesian Positive Law. The finding from this research is that the public's understanding of the rules for using joint marital property objects is not in accordance with normative rules.